The influence of political and legal ideas of national educators on the establishment and development of the Belarusian statehood in the 12th – 18th centuries - Golubeva, Ludmila L. (Journal of the Belarusian State University. Law, 2024)
The author shows the influence of political and legal ideas of national educators on the establishment and development of state bodies of power, law, politics, and legislation in various periods of the establishment and development of Belarusian statehood from the 12th to the 18th century. It is noted that Belarusian educators in their works meaningfully reflected the most significant social and political problems of the era of their modern society, advocated the creation of an independent state, for the preservation of its independence as the main political value, raised the issue of improving state and legal institutions, noted the need to preserve and study the historical heritage of the Belarusian people in order to avoid mistakes in the future.